Engineered Mesenchymal Stem Cells as a Biotherapy Platform for Targeted Photodynamic Immunotherapy of Breast Cancer. Issue 6 (12th January 2022) - Zhang, Hanxi; Feng, Yi; Xie, Xiaoxue; Song, Ting; Yang, Geng; Su, Qingqing; Li, Tingting; Li, Shun; Wu, Chunhui; You, Fengming; Liu, Yiyao; Yang, Hong
Abstract: Interleukin‐12 (IL12) is a pleiotropic cytokine with promising prospects for cancer immunotherapy. Though IL12 gene‐based therapy can overcome the fatal hurdle of severe systemic toxicity, targeted delivery and tumor‐located expression of IL12 gene remain the challenging issues yet to be solved. Photo‐immunotherapy emerging as a novel and precise therapeutic strategy, which elaborately combines immune‐activating agents with light‐triggered photosensitizers for potentiated anticancer efficacy. Herein, an engineered stem cell‐based biotherapy platform (MB/IL12‐MSCs) incorporating immune gene plasmid IL12 (pIL12) and photosensitizer methylene blue (MB) is developed to realize tumor‐homing delivery of therapeutic agents and photo‐immunotherapy efficacy enhancement. The biotherapy platform retained tumor‐tropic migration and penetration functions, which improved the intratumoral distribution of therapeutic agents, thereby promoting photodynamic effects and reinforcing immune responses. Importantly, MB/IL12‐MSCs restricted the expression and distribution of IL12 at tumor site, which minimized potential toxicity while eliciting sufficient anticancer immunity. In noteworthy, activation of immunity induced by MB/IL12‐MSCs established long‐term systemic immunologic memory to prevent tumor relapse. The MB/IL12‐MSCs outperform their monotherapy counterparts in breast tumor models, and the growth of tumor significantly arrested as well as re‐challenging abscopal tumor growth slowdown. Collectively, this work reveals that MSCs‐based strategy may advance more efficient, durable, and safer cancer photo‐immunotherapy. Abstract : A novel engineered stem cell‐based biotherapy platform (MB/IL12‐MSCs) is developed, incorporating immune gene plasmid IL12 and photosensitizer methylene blue (MB) for tumor homing delivery of therapeutic agents and photo‐immunotherapy efficacy enhancement. Importantly, activation of immunity induced by MB/IL12‐MSCs establishes long‐term systemic immunologic memory to inhibit tumor relapse. This work reveals that an MSCs‐based strategy might advance more efficient, durable, and safer cancer photo‐immunotherapy.